SCAR marker development for quick detection of Fusarium oxysporum f. sp. lentis - JADHAV, SUNIL; KUMAR, ATUL; KUMAR LAL, SANDEEP; AKHTAR, JAMEEL; ASKI, MURALEEDHAR; MISHRA, GYAN PRAKASH; JAVERIA, SHAILY (The Indian Journal of Agricultural Sciences, 2022)
The Fusarium wilt caused by Fusarium oxysporum f. sp. lentis is recognized as a major seed and soil-borne disease of lentil worldwide. Rapid detection of Fusarium wilt is important for the management of disease at an early stage and thereby preventing the epiphytotic. Forty cultures of Fol were purified after routine isolation from infected seeds from different geographical locations. The amount of genetic diversity was evaluated using PCR amplification with a set of 6 RAPD primers of selective nucleotide primer pairs. The phylogenetic relationship of RAPD marker revealed diversity among the isolates. The RAPD monomorphic bands were cloned and sequenced. The final SCAR marker designed, provides the amplicon size 353bp with Fol isolates. The RAPD derived SCAR marker is the first marker with high sensitivity genomic DNA and species specific for the detection of Fol. This species-specific SCAR marker can be employed for the quick detection of fungus in seed during seed certification or seed health testing for long-term conservation of lentil.